Motor profile of quilombola children in the community of Tiningú in Santarém-PA (Research, Society and Development, 2021)
Analyzing motor development is essential to establish changes in behavior related to age, growth, posture, movement of the child, and the maturation of the body's mechanisms and systems. In view of this, it is necessary to assess the motor development of children in a quilombola community, as it allows professionals in the field to investigate aspects and characteristics related to the development of this public. The aim of this study was to analyze the motor profile of quilombola children from Tiningú, Santarém/PA. The methodology is a descriptive and exploratory research with a quantitative and qualitative character. The sample consisted of 18 children of both sexes. The data collection tool was the child EDM test battery proposed by Rosa Neto (2002), it was necessary to divide into 2 days of data collection. Data underwent simple descriptive statistical analysis in Microsoft Office Excel 2010 and BioEstat version 5.0. The results, there are the classifications of the MGQ of the 18 children, where 11 children obtained 61.11%, being in the average normal classification, 2 children reached 11.11%, being compatible with the CI, and 5 children reached 27.78%, being normal low. None had higher, lower and much lower motor age. It was concluded, from the results obtained, that the motor development of the evaluated children is within the parameters of normality, that is, compatible with the chronological age in which they found themselves. Therefore, there were 2 groups of significant response, children who were above and below normality.